2017
DOI: 10.1111/gwmr.12195
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Chemical Oxidation: Permanganate Oxidant Volume Design Considerations

Abstract: Contaminant rebound and low contaminant removal are reported more frequently with in situ chemical oxidation than other in situ technologies. Although there are multiple causes for these results, a critical analysis indicates that low oxidant volume delivery is a key issue. The volume of oxidant injected is critical and porosity of the aquifer matrix can be used to estimate the pore volume. The total porosity (qT) is the volume of voids relative to the total volume of aquifer material. The mobile porosity (qM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…However, due to the very restricted natural attenuation conditions for CF and its complex distribution in the subsurface as a dense nonaqueous phase liquid (DNAPLs), more efficient engineered remediation strategies have been proposed to increase CF removal in the environment. As a result of the high oxidation state of carbon in CF, its degradation by in situ chemical oxidation (ISCO) is in general much less effective than for chlorinated ethenes using common oxidants such as permanganate, iron-activated persulfate (PS), ozone, hydrogen peroxide, or Fenton's Reagent 19 . However, thermally-activated PS was recently shown to be a better option for efficient CF oxidation with the advantage that under thermal activation, the strongly oxidizing sulfate radical and other reactive intermediates (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the very restricted natural attenuation conditions for CF and its complex distribution in the subsurface as a dense nonaqueous phase liquid (DNAPLs), more efficient engineered remediation strategies have been proposed to increase CF removal in the environment. As a result of the high oxidation state of carbon in CF, its degradation by in situ chemical oxidation (ISCO) is in general much less effective than for chlorinated ethenes using common oxidants such as permanganate, iron-activated persulfate (PS), ozone, hydrogen peroxide, or Fenton's Reagent 19 . However, thermally-activated PS was recently shown to be a better option for efficient CF oxidation with the advantage that under thermal activation, the strongly oxidizing sulfate radical and other reactive intermediates (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Lessons are learned by addressing challenges that occur throughout the project lifecycle. Previous papers have compiled some of the ISCO design and performance challenges (Huling, Ross, & Prestbo, ; Krembs, Siegrist, Crimi, Furrer, & Petri, ; McGuire, McDade, & Newell, ) suggesting heterogeneity, insufficient volume, and decreased bioremediation, respectively, as impediments to successful ISCO. This paper compiles a range of challenges encountered during ISCO projects, categorizing contributory factors and attempting to elucidate specific details where possible.…”
Section: Isco Lessons Learnedmentioning
confidence: 99%
“…The injectate volume should be compared to effective pore volume in the intended treatment area to verify the approach. Applying too small of a volume of injectate fails to deliver the oxidant to, and distribute the oxidant in, the target treatment volume (Huling et al., ). Similarly, applying too large a volume of injectate can promote displacement of the existing groundwater (potentially spreading the compounds beyond the treatment area) and increases the potential for breakout, or surfacing, of injectate.…”
Section: Isco Lessons Learnedmentioning
confidence: 99%
“…A critical review of two decades of contaminated groundwater sites treated by in situ chemical oxidation (ISCO) has uncovered many examples where liquid oxidant injections have failed to achieve desired cleanup goals [1,2]. Unlike the positive results obtained when chemical oxidants are used in well-mixed reactors, such as during the treatment of municipal wastewaters, direct-push delivery techniques of liquid oxidants into groundwater can fail to deliver uniform coverage.…”
Section: Introductionmentioning
confidence: 99%
“…Huling et al [1] systematically reviewed a series of ISCO performance surveys and concluded that poor ISCO performance often corresponds with sites treated with low oxidant volumes (i.e., percentage of contaminant plume). A review of 40 ISCO sites showed that nearly 50% of the ISCO treatments injected liquid oxidant volumes equivalent to 10% of the contaminant plume [2][3][4].…”
Section: Introductionmentioning
confidence: 99%